Electrochemical Fabrication of Shape-Controlled Copper Hierarchical Structures Assisted by Surfactants. (8th December 2011) - Dong, Huaping; Wang, Yajun; Tao, Feifei; Wang, Linxia
Abstract : Various copper hierarchical structures assisted by surfactants were successfully fabricated combined with the electrodeposition technique. To the best of our knowledge, it is the first report on the controlled synthesis of metal copper hierarchical structures. All of the products synthesized in the presence and absence of surfactants, such as cetyltrimethylammonium bromide (CTAB), sodium dodecyl sulfate (SDS), or polyvinylpyrrolidone (PVP), were face-centered cubic copper, characterized by X-ray diffraction (XRD), indicating the surfactant-independent crystal structure. However, supplementing surfactants is helpful to construct hierarchical structures and exerts an important influence on copper morphologies. The absence of surfactants led to the formation of the nubby structures, while the use of surfactants resulted in the synthesis of the flower, dendrite, and sphere-like hierarchical morphologies. The effect of deposition time on the copper morphologies was investigated by scanning electron microscopy (SEM), and the possible formation mechanism of the copper hierarchical structures with various morphologies was discussed.